The use of GIS network analysis methods that assess the availability of places of open physical activity in Bydgoszcz - Sebastian Czapiewski (Kazimierz Wielki University, 2018)
Development of an analysis of the availability of physical activity for the inhabitants of Bydgoszcz using the methods of GIS network analysis. A characteristic feature of the development is the use of network analysis methods commonly used instead of the methods for estimating the distance based on the buffers. Thanks to the technology used, obtained communication availability of land sports and recreation for individual areas of the city. Considerable differences in the availability of open areas of physical activity in Bydgoszcz, some areas located in the city center, in a significant concentration of the population has a very good accessibility. Worst availability located in areas characterized by a predominance of the production function and significant areas of forest.